Karakteristik kimia dan fisika semen pozolan kapur yang diperkaya silika abu sekam padi - Asma Assa; Erwin Adinata (Jurnal Dinamika Penelitian Industri, 2013)
Development of infrastructures intensively in the last decades has increased the demand for building materials, such as cement. This also causes the prices of Portland Cement, the most common type of cements has also increased and sometimes it is difficult to find it in the markets. Another type of cement namely Lime Pozolan Cement (SPK) may be used to substitute for Portland Cement for building construction which receives relatively low loads. The SPK is produced from pozolan materials and lime without heating process. The common pozolan materials used is tras. This research is aimed to investigate chemical and physical characteristics of the SPK enriched with silica of rice hull ash (ASP). The ASP is intended to reduce the use of trace as the source of silica. Methods used included experiments and testing. Supplements of the ASP in the SPK were varied at the levels of 0, 5, 10, 15, and 20% (w/w). The results of the research indicated that without ASP supplement (control treatment), SiO2 contents was 53.94%. By 5 to 20% ASP supplement increased SiO2 content to 59.54 - 65.87%. However SO3 content was reduced from 3.43% to 2.04 - 1.11% and MgO content from 2.36% to 2.29 - 1.64%. Furthermore, as the ASP supplement in SPK increased the compresive strength of concrete samples also increased, except at 15% and 20% ASP supplement after 21 and 28 days storage of the samples. Therefore, the optimum ASP supplement in SPK in this study was 15% with compressive strength of 103 x105 kg/m2 after 21 days storage and 128 x105 kg/m2 after 28 days storage.Keywords : chemical and physical characteristics, lime pozolan cement, rice husk ash silikaAbstrakKemajuan pembangunan sarana dan prasarana konstruksi yang sangat pesat pada beberapa dekade terakhir ini menyebabkan kebutuhan akan bahan bangunan termasuk semen juga meningkat bahkan kadang-kadang sulit ditemukan di pasaran. Salah satu jenis semen yaitu Semen Pozolan Kapur (SPK) dapat digunakan untuk mensubsitusi semen portland untuk konstruksi bangunan yang menerima beban relatif lebih kecil. SPK diproduksi dari bahan pozolan dan kapur padam tanpa proses pemanasan. Bahan pozolan yang sering digunakan adalah tras. Penelitian ini bertujuan untuk mengetahui karakteristik kimia dan fisika SPK yang diperkaya silika dari Abu Sekam Padi (ASP). ASP ini dimaksudkan untuk mengurangi pemakaian tras sebagai sumber silika. Metode penelitian meliputi eksperimen dan pengujian. Penambahan ASP didalam SPK divariasikan pada level 0, 0,5, 10, 15 dan 20% (w/w). Hasil penelitian menunjukkan bahwa tanpa penambahan ASP (kontrol), kandungan SiO2 SPK sebesar 53,94%. Dengan penambahan 5 sampai 20% ASP kandungan SiO2 meningkat menjadi 59,54 - 65,87%. Sebaliknya kandungan SO3 yang semula 3,43% turun menjadi 2,04 - 1,11% dan kandungan MgO turun dari 2,36% menjadi 2,29 - 1,64%. Selanjutnya penambahan ASP didalam SPK meningkatkan kuat tekan beton, kecuali pada penambahan 15% dan 20% setelah umur beton 21 dan 28 hari. Karena itu penambahan optimum ASP untuk sifat fisika SPK adalah 15% dengan kuat tekan 103 x 105 kg/m2 sesudah 21 hari dan 128 x 105 kg/m2 sesudah 28 hari.Kata kunci : abu sekam padi, karakteristik kimia dan fisika, semen pozolan kapur